1990
DOI: 10.21273/jashs.115.3.348
|View full text |Cite
|
Sign up to set email alerts
|

Strain and Rootstock Effects on Spur Characteristics and Yield of `Delicious' Apple Strains

Abstract: The characteristics of 1-year-old vegetative spurs growing on 2-year-old branches were measured on 28 `Delicious' apple (Malus domestica Borkh.) strains growing on M.7 rootstocks at Clarksville, Mich., and on 23 strains of `Delicious' on M.7a rootstocks at Kearneysville, W.Va. Spur-type strains typically had densities >20 to 21 spurs/m, and high spur leaf numbers, leaf areas per spur, leaf areas per leaf, and terminal bud diameters, whereas values for standard strains were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
24
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 3 publications
4
24
1
Order By: Relevance
“…This was done in Washington, Oregon, and Indiana, but not in other states. Warrington et al (1990), using data from the Clarksville planting in 1986, demonstrated significant correlations (r) between spur density and a) trunk cross-sectional area (-0.56 ** ) and b) yield efficiency (0.23 ** ), spur strains having consistently higher yields and spur densities, and lower cross-sectional areas, than standard strains. Our data for 1984-87 confirm that trees of spur strains generally yielded more fruit per unit trunk cross-section and were smaller than standard trees.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This was done in Washington, Oregon, and Indiana, but not in other states. Warrington et al (1990), using data from the Clarksville planting in 1986, demonstrated significant correlations (r) between spur density and a) trunk cross-sectional area (-0.56 ** ) and b) yield efficiency (0.23 ** ), spur strains having consistently higher yields and spur densities, and lower cross-sectional areas, than standard strains. Our data for 1984-87 confirm that trees of spur strains generally yielded more fruit per unit trunk cross-section and were smaller than standard trees.…”
Section: Discussionmentioning
confidence: 98%
“…Trees of 28 strains (Table 1) propagated on two rootstocks, M.7 EMLA and MM.111 EMLA, hereafter referred to as M.7 and MM.111, were planted at nine locations in Washington, Oregon, Idaho, Indiana, Michigan, and British Columbia. Data for the Washington and Idaho sites (Fallahi et al, 1994(Fallahi et al, , 1995Ketchie, 1986), data for a similar study in West Virginia (Baugher et al, 1990), and data for the British Columbia site (Lane and MacDonald, 1996) have been published. Yield data for Michigan for 1 year were included in an analysis of strain and rootstock effects on spur characteristics and yield conducted in 1986 (Warrington et al, 1990), and all data on fruit color have been published (Dennis, 1989), as well as a brief summary .…”
mentioning
confidence: 99%
“…'Delicious' strains are selected for specific characteristics, primarily bearing habit (spur or standard type), yield, fruit color, and shape (Crassweller and Hollender, 1989;Crassweller et al, 1985;Fisher and Ketchie, 1981;Fisher et al, 1970;Ingle, 1972;Ketchie, 1984;Lord et al, 1980;Tukey and Ballard, 1969;Westwood, 1963Westwood, , 1967Westwood and Burkhart, 1968). Warrington et al (1990) reported that spur-type strains had higher spur densities (spur/m of branch), spur leaf number, leaf areas per spur, leaf areas per leaf, and terminal bud diameters than those of standard-type strains. They also found a positive correlation between spur density and yield efficiency.…”
mentioning
confidence: 99%
“…A second factor is the root system, which has been used as an efficient although empirical means to control tree size, with variable results on flowering (i.e., dependent on the genotype; Webster et al, 1985). The effects of the root system have been studied using various plant materials: own-rooted trees (usually micropropagated; Webster et al, 1985;Zimmerman and Miller, 1991;Quamme and Brownlee, 1993;Hirst and Ferree, 1995a) and/or trees grafted on rootstocks (Lockard and Schneider, 1981;Cummins and Aldwinckle, 1983;Lehman et al, 1990;Warrington et al, 1990;Barritt et al, 1995;Ferree et al, 1995;Hirst and Ferree, 1995a;Costes et al, 2001) or on various rootstock-interstock combinations (Seleznyova et al, 2003). The root system, from ''dwarf'' to ''vigorous,'' strongly influences overall tree size, with own-rooted trees generally equivalent to or larger than trees of the same genotype grafted on the most vigorous clonal rootstocks (Ferree, 1988;Larsen and Higgins, 1990;Quamme and Brownlee, 1993) or on seedling rootstocks (Zimmerman and Miller, 1991).…”
mentioning
confidence: 99%